Pengaruh Model Pembelajaran Think Pair Share (TPS) Berbantuan Media Card Sort terhadap Kemampuan Membaca Permulaan (Penelitian Pada Siswa Kelas II di SD Negeri Trasan 2 Kecamatan Bandongan Kabupaten Magelang) - Ansurya Yunita; Arif Wiyat Purnanto; Galih Istiningsih (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of the Think Pair Share (TPS) learning model assisted by Media Card Types on the Beginning Reading Ability of second grade students at SD Negeri Trasan 2, Bandongan District, Magelang Regency. This study uses a Pre- Experimental Design research type with the One Group Pretest Posttest Design model. The research subjects were selected using a non-probability sampling saturated sampling model. The samples taken were 16 students. by using data collection methods in the form of performance tests. Data analysis using parametric statics techniques, namely Paired Sample t Test. The results showed that the average calculation of the posttest performance test was 76.56 which was greater than the pretest performance test results with an average value of 47.85. This is evidenced by the results of the Wilcoxon test analysis which shows Zcount of -4.436 with a significance value of 0.00 <0.05, meaning that there is a significant difference between the results of the pretest and posttest using the Think Pair Share (TPS) Learning Model assisted by Media Card Sort. The results of this study can be concluded that the use of Think Pair Share (TPS) learning model assisted by Media Card Sort has a significant effect on Beginning Reading Ability.